ANALISA PENGARUH BRAND EXPERIENCE TERHADAP CUSTOMER LOYALTY MELALUI BRAND TRUST, CUSTOMER SATISFACTION DAN CUSTOMER INTIMACY SEBAGAI VARIABEL INTERVENING PADA KIEHL’S SURABAYA - Carlos Bryan Sidabutar (Jurnal Strategi Pemasaran, 2015)
This study aims to analyze the influence of the brand experience to brand trust, customer satisfaction and customer intimacy that impact on customer loyalty at Kiehl's Surabaya. This study will be conducted by distributing questionnaires to 100 consumer respondents Kiehl's Surabaya. The analysis technique used is the technique of quantitative analysis method path analysis (path analysis) and partial least square (PLS).The research proves that there is a significant influence of the brand experience to brand trust on Kiehl's, there was a significant effect of brand experience to customer satisfaction, there is a significant influence of the brand experience to customer intimacy,  significant effect of brand trust on customer intimacy,  significant effect of customer satisfaction on customer intimacy, and there was a significant effect of customer intimacy to customer loyalty.